Quantitative Analysis of Aerosol Influence on Suomi-NPP VIIRS Nighttime Light in China - Xuejun Wang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2020)
As a primary nighttime light (NTL) data source, the day/night band (DNB) sensor of the visible infrared imaging radiometer suite (VIIRS) is used in a wide range of studies. However, this signal is influenced by the atmosphere and may cause uncertainty while monitoring ground NTL. Given the lack of the quantitative analysis of the atmospheric effect on NTL, this study analyzes the relationship between VIIRS DNB NTL radiance and aerosol optical depth (AOD) in the urban areas of Beijing and three other Chinese cities of different urbanization levels. Results suggest a significantly negative relationship between the NTL radiance and AOD. The linear and log-linear models generate similar coefficients of determination (R2) for the AOD and NTL data, which vary for different urban centers. In Beijing, where the aerosol robotic network observations are available, R2 reached 0.655 between the monthly NTL radiance and AOD. A slight decrease of R2 occurred while using the Himawari AOD. The relationship between the NTL radiance and AOD varies among the cities. The NTL radiance may decrease by approximately 10 nW.cm-2sr-1 when daily AOD increases one unit. For Beijing, this decrease may be above 15 nW.cm-2sr-1, which is comparable with the threshold used to extract urban areas. These findings underscore the importance of AOD in the application of NTL data that are potentially useful in the reconstruction of stable time series VIIRS DNB images by removing the aerosol effects.